2018
DOI: 10.3892/or.2018.6760
|View full text |Cite
|
Sign up to set email alerts
|

Expression of KLF9 in pancreatic cancer and its effects on the invasion, migration, apoptosis, cell cycle distribution, and proliferation of pancreatic cancer cell lines

Abstract: Kruppel-like factor 9 (KLF9), a transcription factor, is critical for the inhibition of growth and development of tumors, whereas its effects in pancreatic cancer remains unclear. The purpose of the present study was to investigate the expression and functional significance of KLF9 in vitro, by assessing the expression of KLF9 in pancreatic cancer tissue samples and its association with the total survival of patients and clinicopathological data. The levels of KLF9 expression in adjacent tissues and pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…Although various modes of action are still debated, it is broadly accepted that GCs mediate their anti-inflammatory and immunosuppressive effects by affecting macrophage viability and antitumor functionality (4). Several studies have demonstrated that tumor-derived KLF9 may act as a tumor suppressor by promoting apoptosis (8,19,20). Decreased KLF9 suppresses oxidative stress and apoptosis, subsequently promoting cancer progression (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various modes of action are still debated, it is broadly accepted that GCs mediate their anti-inflammatory and immunosuppressive effects by affecting macrophage viability and antitumor functionality (4). Several studies have demonstrated that tumor-derived KLF9 may act as a tumor suppressor by promoting apoptosis (8,19,20). Decreased KLF9 suppresses oxidative stress and apoptosis, subsequently promoting cancer progression (7).…”
Section: Discussionmentioning
confidence: 99%
“…KrĂŒppel-like factor 9 (KLF9), also called basic transcription element-binding protein-1 (Bteb1), is a ubiquitously expressed member of the C2H2-type zinc finger family (7). A recent study suggested that KLF9 plays an important role in regulating animal development and differentiation of various cell types (8). KLF9 can be induced by several physiological or pathological stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant increased or decreased expression of miRNAs has been implicated in different human diseases, particularly cancer ( 16 ). Previous studies demonstrated that miR-34a-5p acted as a tumor suppressor in various types of cancer, such as colorectal cancer ( 17 ), cervical cancer ( 18 ) and pancreatic carcinoma ( 19 ). However, the role of miR-34a-5p in lung cancer is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…KLF9 role is notable in lung and pancreas tumors. [46] The role of these genes in HNSCC remains to be explored.…”
Section: Discussionmentioning
confidence: 99%